Analysis of Local Natural Resource Utilization in Project Based Learning (PjBL) in Higher Education in Indonesia-Malaysia Border Regions - Ulfah, Zakiyah; Hidayah, Maulida Ulfa (FKIP - Universitas Riau, 2025)
The Indonesia-Malaysia border area has diverse and beneficial local natural resource potentials, but hasn’t been fully utilized in learning at universities. The purpose of this study is to analyze the utilization of local natural resources in the application of the PjBL model in state universities in the Indonesia-Malaysia border area, more precisely in West Kalimantan, namely IAIN Pontianak. The focus of the study is the utilization of local natural resources as teaching materials and project media, as well as its impact on student involvement in the learning process and learning outcomes. This study adopts a descriptive qualitative methodology, gathering data via in-depth interviews, observations, and documentation. The data analysis technique used is the technique from Miles, Huberman and Saldana with data validity through triangulation. The results of the study show that the utilization of local natural resources in PjBL can increase active student involvement, strengthen the relevance of lecture materials to real contexts, encourage the emergence of creative and innovative solutions to local potentials and problems, and foster awareness of environmental conservation among students. However, its implementation is still not optimal due to limited supporting facilities and infrastructure, uneven lecturer competence, and minimal collaboration with the local community and industry.